The Effect Of Product Quality And Price Perception On Purchasing Decisions Of Emina Cosmetic Products On Shopee With Brand Image As An Intervening Variable - Kusumadevi, Mutiara , Porista; Diposumarto, Ngadino Surip; Pranowo, Agus Setyo (UNIVERSITAS PAKUAN, 2024)
This research aims to determine the effect of product quality and price perception on the purchasing decisions of Emina products on Shopee through brand image. The method used in this study was a quantitative approach. The population in this research consisted of active undergraduate students majoring in Management at Pakuan University who purchased Emina products through Shopee. The sampling technique used in the study was Cluster Sampling, and the total number of respondents was 178. The analysis techniques utilized were Descriptive Statistics and Structural Equation Modeling (SEM). Questionnaire data were analyzed using SPSS Version 22 and Lisrel 8.80 software. The results of this research indicate that (a) product quality affects purchasing decisions with a calculated t-value critical t-value, namely 2.72 1.96. (b) price perception affects purchasing decisions with a calculated t-value critical t-value, namely 5.93 1.96. (c) product quality affects brand image with a calculated t-value critical t-value, 2.39 1.96. (d) price perception affects brand image with a calculated t-value critical t-value, 7.62 1.96. (e) brand image affects brand purchasing decisions with a calculated t-value critical t-value, 2.69 1.96. (f) product quality and price perception affect brand image with a calculated t-value critical t-value, 6.57 1.96. (g) product quality, price perception, and brand image affect purchasing decisions with a calculated t-value critical t-value, namely 4.50 1.96.